Sustained Monopolistic Business Relationships: A UK Defence Procurement Case - Humphries, Andrew (Cranfield University, 2003)
Business-to-business relationships within sustained monopolies, such as those within Defence Procurement, have received limited attention by Management Researchers. This is unusual because under these market circumstances typically there appear to be few incentives to achieve mutually beneficial outcomes despite their strategic policy importance. The purpose of this thesis is therefore, to determine the influential relationship factors between the UK Ministry of Defence and its Industrial partners within a predominantly monopolistic Defence Procurement business. The approach adopted for this research project is exploratory and inter-subject area. It uses quantitative and supportive qualitative data to examine the problem through an economic model using Supply Chain Management, Relationship Marketing and Transaction Cost Economics. A self-selected census of 54 business relationships is carried out from both the buyer and supplier perspectives through staff questionnaires and team leader semi-structured interviews. The findings from this research show, contrary to the expectation of the theoretical model, a positive relationship success situation with a spectrum of both positive and negative behavioural factors present. However, a significant adversarial influence is a suite of issues that are endemic to the business in question such as old products, obsolescence, staff and organisational upheavals, poor end-customer visibility and lack of investment in modern procedures and systems. Within the monopoly environment these accentuate managers’ frustrations due to lack of freedom of action. The primary contribution of this research is therefore, an increased understanding of the business-to-business relationship dynamics within long-term, closely coupled, collaborative, business-to-business arrangements as exemplified by UK Defence and the results are likely to be of interest to both academics and managers.
Keywords: Transaction Cost Economics; Business to business; B2B; monopolies; Defence procurement; Supply Chain Management; Relationship Marketing; Transaction Cost Economics